Mental Cinema of the Imagination. Film in Poetry and the Issue of “Film” Ways of Seeing - Koschany, Rafał (Porównania, 2021)
The starting point and, at the same time, research material that I would like to analyze is Polish film poetry. The formula itself indicates a specific intersemiotic relations, but apart from the obvious issues (such as the presence of film themes and structures in poetry), the linguistic film metaphors that repeat in poetry and become specific signs of imagination seem equally interesting. Film poetry is an interesting testimony of a long-lasting relationship between the experience of cinema and the experience of reality. Above all, however, it is a linguistic community within which the message that something can be “like in the cinema” or “film-like” is universally understandable. I additionally assume that the study of poetry and the schematic formulas used in it may suggest something about the cinematic perception of reality in general. Just as the film changed the human perception of the world, the way of perception, understanding the principles of storytelling, dreaming and “imagining”, we find traces of these transformations in the texts of writers who were subject to the same common influences, and at the same time sought their linguistic equivalents.